PENGARUH MODAL KERJA TERHADAP LABA PADA PT. TELEKOMUNIKASI INDONESIA (PERSERO) Tbk: modal kerja dan laba - sutrisno s.pd., m.pd (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2021)
This research was conducted with the aim of knowing the effect of working capital on profits at PT Telekomunikasi Indonesia (Persero) Tbk. This research is a quantitative research with the population is all consolidated financial statement data of PT Telekomunikasi Indonesia (Persero) Tbk for the period 2010-2017. While the sample in this study is a statement of financial position consisting of balance sheet and income statement of PT Telekomunikasi Indonesia (Persero) Tbk for the period 2010-2017. The data collection technique used is documentation techniques and uses simple linear regression data analysis with the help of the SPSS program. The results of this study indicate that working capital has a positive and insignificant effect on profits at PT Telekomunikasi Indonesia (Persero) Tbk. This means that changes in working capital at PT Telekomunikasi Indonesia (Persero) Tbk make a small or insignificant contribution to profit.Keywords: Working Capital, Profit